Dualism in Education: Management of School and Madrasah Education - Resnita, Resnita (Journal of Innovation in Teaching and Instructional Media, 2024)
The issue of educational dualism has been frequently discussed in the world of education recently due to its compartmentalized nature. This article provides information by reviewing the dualism of education management between schools and madrasahs. The writing method of this journal utilizes a qualitative research technique in the form of library research, drawn from various book and journal references on educational policy analysis. The research focuses on the analysis of educational policies from the madrasah perspective. The findings indicate that dualism involves two conflicting principles. In terminology, dualism can be defined as two principles or understandings that are different or not synchronized. Thus, dualism is a state of being two and a system based on two principles that assert the existence of two substances. In the field of education in Indonesia, this issue is handled by two ministries, namely the Ministry of Education and Culture and the Ministry of Religious Affairs.